ORGANIZATION OF TRANSPLANTATION ASSISTANCE THROUGH TRANSPORTATION OF THE RECIPIENT TO THE REGIONAL EXPLANTATION BASE FOR HEART TRANSPLANTATION - Kovtun, Gavrylo; Shpachuk, Anton; Chaikovska, Sofia; Sudakevych, Serhii; Todurov, Borys (Eastern Ukrainian Medical Journal, 2024)
Introduction. To date, heart transplantation remains the only effective method of treatment for patients with end-stage chronic heart failure. Due to the short time of ischemia of the donor heart and the lack of an alternative to deliver the organ on time over long distances, the strategy in organizing transplantation was changed. The aim of this study was to analyze the effectiveness of transporting the recipient to the donor to reduce the ischemia time of the donor organ during martial law. Materials and methods. This retrospective study includes all cases of heart transplantation carried out by specialists of the State Institution "Heart Institute of the Ministry of Health of Ukraine" during 2022–2024. Heart transplantations were performed directly in our center and on-site. Outpatient surgery involved heart transplantation in the medical facility where the donor was located or in the nearest hospital. The results. The study included 55 patients who underwent orthotopic heart transplantation, of which 20.0% were women and 80.0% were men. Depending on the place of heart transplantation, all patients were divided into two groups: the first group (32 patients) – heart transplantation in the State Institution "Heart Institute of the Ministry of Health of Ukraine" and the second group (23 patients) – heart transplantation elsewhere. The duration of donor heart ischemia was not significantly different between the study groups (95.4±15.3 min vs. 90.3±10.8 min, p=0.167), although there was a tendency to decrease in the patients of the second group. Hospital survival was 93.8±4.28% among patients of the first group and 91.3±5.87% among patients of the second group (p=0.408). 12-month survival in the study groups was 87.5±5.84% versus 86.9±7.02% (p=0.375). Conclusions. The use of recipient-to-donor transportation not only made it possible to reduce the duration of ischemia of the donor heart, but also presented with a similar level of hospital and 12-month survival, which makes it possible to effectively apply this method in wartime conditions when there is no possibility of helicopter transportation.